SECRETARY FUNCTION OF THE STOMACH IN YOUNG CHILDREN, PATIENTS WITH IRON DEFICIENCY ANEMIA, DEPENDING ON THE TREATMENT METHODS - Kudratova G.N,; Ibragimova D.S,; Kholmuradova Z.E,; Turaeva D.Kh, (International Journal of Innovations in Engineering Research and Technology, 2021)
According to the WHO, more than 1.5 billion people with anemia are registered every year, almost 50% of cases are due to iron deficiency. The UNICEF Micronutrient Initiative shows the relationship between iron deficiency anemia and such economically significant factors as decreased real performance, increased maternal mortality, and negative impact on the physical and mental development of the child.In the treatment of patients with iron deficiency anemia, it is necessary to eliminate the etiological and pathogenetic causes, because without this, it is impossible to treat anemia (2.6).In case of mild and moderate anemia, to restore the secretory function of the stomach and clinical and hematological parameters, it is sufficient to correct nutrition according to age, include fruit vegetable juices, prescribe a solution of hydrochloric acid or natural gastric juice, iron preparations (3.5).    Patients with severe anemia of complex treatment, including prednisone, had even better treatment results. Clinical and hematological changes recovered faster, the secretory function of the stomach returned to normal in most patients.Therefore, when prescribing therapy for patients with iron deficiency anemia, it is necessary to take into account drugs that improve the secretory function of the stomach, which increase the digestion and absorption capacity of the gastrointestinal tract.